Conductive layer protected and oxide catalyst-coated thin-film silicon solar cell as an efficient photoanode. Issue 23 (20th October 2017) - Wang, Ning; Liu, Min; Liang, Junhui; Li, Tiantian; Tan, Hairen; Liu, Bofei; Zhang, Qixing; Wei, Changchun; Zhao, Ying; Zhang, Xiaodan
Abstract : Photovoltaic–photoelectrochemical (PV-PEC) water splitting based on silicon (Si) is very promising because of its broad visible light absorption, earth abundance and high carrier mobility. Abstract : Photovoltaic–photoelectrochemical (PV-PEC) water splitting based on silicon (Si) is very promising because of its broad visible light absorption, earth abundance and high carrier mobility. However, its practical application is hindered by its poor performance in the oxygen evolution reaction (OER) and poor stability in electrolytes. Here, we introduced a conductive indium tin oxide (ITO) protective layer for superior interface charge transfer and developed a synergistic strategy by combining the protective layer with a NiO x catalyst layer for favorable kinetic overpotential. Thus, we delivered a photocurrent density as high as 7.64 mA cm −2 at 1.23 V versus RHE on the double junction microcrystalline silicon (μc-Si : H) solar cell PEC device in 1 M NaOH electrolyte. This current density is 37 times higher than that of the device with only NiO x under the same conditions. The μc-Si : H solar cell with ITO and NiO x layers has a maximum efficiency of 2% at an applied bias of 0.85 V vs. RHE. Our work will open up new opportunities for designing and preparing high-performance and non-noble PEC water splitting devices.